Lupus nephritis: clinical presentations and outcomes in the 21st century - Gasparotto, Michela; Gatto, Mariele; Binda, Valentina; Doria, Andrea; Moroni, Gabriella (Rheumatology (Oxford, England), 2020)
Abstract Lupus nephritis (LN) is a frequent and severe manifestation of SLE. Along the decades, the epidemiology of LN and its clinical presentation have been changing. However, even though retrospective cohort studies report a decreased mortality rate and an improvement in the disease prognosis, the percentage of patients progressing into end stage renal disease (ESRD) keeps steady despite the improvements in therapeutic strategies. Current in-use medications have been available for decades now, yet over the years, regimens for optimizing their efficacy and minimizing toxicity have been developed. Therapeutic research is now moving towards the direction of precision medicine and several new drugs, targeting selectively different pathogenetic pathways, are currently under evaluation with promising results. In this review, we address the main changes and persistent unmet needs in LN management throughout the past decades, with a focus on prognosis and upcoming treatments.